2016
DOI: 10.1007/s11947-016-1753-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Sweet Cherry Phenolic Degradation During Thermal Treatment Based on Fluorescence Spectroscopy and Inactivation Kinetics

Abstract: Five anthocyanins were detected in the sweet cherry extract as follows: cyanidin 3-rutinoside, cyanidin 3-glucoside, peonidin 3-rutinoside, peonidin 3-glucoside, and pelargonidin 3-rutinoside, whereas the cyanidin 3-rutinoside was found to be in the highest amount. The effect of thermal treatment on the degradation of the polyphenolic compounds in sweet cherry extract was investigated in the range of 70-120°C by means of fluorescence spectroscopy and spectrophotometric techniques. The fluorescence spectra were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 39 publications
6
28
0
Order By: Relevance
“…2), it is possible to observe no significant difference (p-level > 0.05) even if those of smoothies were always slightly lower than those of fresh fruits (466.74 vs 496.51 mg gallic acid per kg -1 ). This last is in accordance to what could have been expected after a double thermal treatment (blanching and pasteurization by microwaves) applied during processing of cherries (Turturică et al, 2016). (Figs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2), it is possible to observe no significant difference (p-level > 0.05) even if those of smoothies were always slightly lower than those of fresh fruits (466.74 vs 496.51 mg gallic acid per kg -1 ). This last is in accordance to what could have been expected after a double thermal treatment (blanching and pasteurization by microwaves) applied during processing of cherries (Turturică et al, 2016). (Figs.…”
Section: Resultssupporting
confidence: 90%
“…These last two antioxidant categories are highly thermolabile, so they are degraded when submitted to thermal treatments (Boon et al, 2010;Poiana Kadian et al, 2013). Then, it is reasonable to suppose that the great part of the residual antioxidant activity is due to polyphenols, which are relatively more resistant to thermal treatments (Turturică et al, 2016;Picariello et al, 2017) and this could explain our results. Nevertheless, the decrease of antioxidant capacity in smoothies respect to fresh fruits was not so relevant respect what could be expected after the double thermal treatment (blanching and pasteurization by microwaves) applied during processing of cherries.…”
Section: Resultsmentioning
confidence: 73%
“…All the negative ∆S # values (from -281.91 to -293.51 J mol -1 K -1 ) found in the present study showed a lower structural freedom than the reactants, which further confirmed that this is an irreversible process. The same behaviour for the evaluated thermodinamic parameter was reported by Turturicã et al [34]. The stability of anthocyanin pigments is affected by several factors such as heat treatment, storage temperature, light, pH value, chemical structure, oxygen, solvents, and the presence of enzymes, proteins, flavonoids, and metallic ions [31].…”
Section: Effects Of Gamma Radiation On the Thermal Degradation Kinetisupporting
confidence: 79%
“…The degradation kinetics of phytochemicals content in lavender extract was fitted to a first-order fractional conversion kinetic model as described by Turturică et al (2016). The degradation kinetics of antioxidant capacity was described by fitting the first order kinetic model (Eq.…”
Section: Mathematical Models and Kinetic Analysismentioning
confidence: 99%